UPAYA PERLINDUNGAN SATWALIAR UNTUK MEMPERTAHANKAN KEANEKARAGAMAN HAYATI DI NEGERI HUTUMURI, KECAMATAN LEITIMUR SELATAN, KOTA AMBON - Latupapua, Lesly; Sahusilawane, Jhon (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
Indonesia is a country blessed with abundant natural wealth and various types, both flora and fauna. This is motivated by the position of Indonesia which is located between two geographic regions of fauna, namely Asia and Australia, with the Wallacea line connecting the two regions. These conditions have made Indonesia one of the countries with the nickname of mega biodiversity in the world. Maluku is included in the geographical area of ​​Australia with a group of islands spread from the north of Halmahera Island to the south of Southwest Maluku Regency, making Maluku rich in fauna potential, one of which is wild animals. However, hunting and illegal wildlife trade pose a serious threat to the preservation of wildlife in Indonesia and Maluku. Wild animals that are traded illegally based on various facts found in the field are caught from nature, not from captivity. Protected and endangered species of wild animals are also still traded freely. Departing from the problems found, community service activities with the topic "Socialization of Wildlife Protection Efforts to Preserve Biodiversity in Hutumuri Country, South Leitimur District, Ambon City. The activity will be held in November 2022. It is hoped that from the PKM activities, the community will understand and be made aware of the potential for natural wealth that they have, it should be preserved and maintained for both current and future generations.